QARSHI SHAHRI SHAROITIDA TARQALGAN VESPIDAE OILASI VAKILLARINING EKOLOGIYASI VA BIOLOGIYASI - Buriyeva X.P, Buriyeva X.P; Arabova N.Z, Arabova N.Z; Xidirova M.X., Xidirova M.X. (Actual problems and prospects of the study of the fauna, 2024)
The article provides information on the ecology and biomorphology of certain true bee species within the family Vespidae, found in the city of Karshi. In urban environments, synanthropic wasps are prevalent, including Polistes dominula, Polistes gallicus, Polistes watti, and Vespula germanica.